Nanoarchitectonics for Ultrathin Gold Films Deposited on Collagen Fabric by High-Power Impulse Magnetron Sputtering - Sheng-Yang Huang; Ping-Yen Hsieh; Chi-Jen Chung; Chia-Man Chou; Ju-Liang He (Nanomaterials, 2022)
Gold nanoparticles conjugated with collagen molecules and fibers have been proven to improve structure strength, water and enzyme degradation resistance, cell attachment, cell proliferation, and skin wound healing. In this study, high-power impulse magnetron sputtering (HiPIMS) was used to deposit ultrathin gold films (UTGF) and discontinuous island structures on type I collagen substrates. A long turn-off time of duty cycle and low chamber temperature of HiPIMS maintained substrate morphology. Increasing the deposition time from 6 s to 30 s elevated the substrate surface coverage by UTGF up to 91.79%, as observed by a field emission scanning electron microscope. X-ray diffractometry analysis revealed signature low and wide peaks for Au (111). The important surface functional groups and signature peaks of collagen substrate remained unchanged according to Fourier transform infrared spectroscopy results. Multi-peak curve fitting of the Amide I spectrum revealed the non-changed protein secondary structure of type I collagen, which mainly consists of α-helix. Atomic force microscopy observation showed that the roughness average value shifted from 1.74 to 4.17 nm by increasing the deposition time from 13 s to 77 s. The uneven surface of collagen substrate made quantification of thin film thickness by AFM difficult. Instead, UTGF thickness was measured using simultaneously deposited glass specimens placed in an HiPIMS chamber with collagen substrates. Film thickness was 3.99 and 10.37 nm at deposition times of 13 and 77 s, respectively. X-ray photoelectron spectroscopy showed preserved substrate elements on the surface. Surface water contact angle measurement revealed the same temporary hydrophobic behavior before water absorption via exposed collagen substrates, regardless of deposition time. In conclusion, HiPIMS is an effective method to deposit UTGF on biomedical materials such as collagen without damaging valuable substrates. The composition of two materials could be further used for biomedical purposes with preserved functions of UTGF and collagen.